Psychological Resilience as a Predictor of Occupational Stress Among Teaching Staff in Course X - Wardani, Indah Kusuma; Nurcandra, Fajaria; Utari, Dr. Dyah; Amrullah, Afif Amir (UI Scholars Hub, 2025)
Workplace stress is a common condition that may be triggered by the demands of professional involvement. Psychological resilience functions as a protective factor that enables individuals to maintain their level of work engagement despite experiencing job-related stress arising from work–life imbalance. This study aimed to examine the relationship between psychological resilience and occupational stress among teaching staff at Course X. The research employed a quantitative approach with a cross-sectional design, utilizing chi-square testing and Cox regression analysis, with a total sample of 98 participants. Data collection was conducted from April to June 2024. The instruments used included the Workplace Stress Scale (WSS), the Work–Life Balance Scale by Fisher, Bulger, and Smith, the Multidimensional Scale of Perceived Social Support (MSPSS), and the Nicholson McBride Resilience Questionnaire (NMRQ). The results indicated that 48.98% of teaching staff experienced occupational stress. A significant association was found between psychological resilience and occupational stress (PR = 2.38). Employment status (PR = 0.46) and work–life balance (PR = 1.50) were identified as confounding factors. The study concludes that teaching staff with low psychological resilience are at greater risk of experiencing occupational stress. Keywords: Occupational stress, Psychological resilience, Teaching staff